ANALISIS KARAKTER RASA INGIN TAHU PADA SISWA KELAS VII DI SMP NEGERI 8 SINGKAWANG TAHUN AJARAN 2O22/2023 - Setyanti, Annisa; Wicaksono, Luhur; Astuti, Indri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to describe the character of taste that you want to know in class VII students of SMP Negeri 8 Singkawang. The method used in this study is a quantitative descriptive method, data collection is an indirect communication technique using closed angles that are shared directly. The results of the research showed the character of curiosity in class VII students of SMP Negeri 8 Singkawang with a proportion of 82.07% in the high category. (1) Characteristics of taste that students want to know reaches 79.86% in the high category. (2) Evaluation of the reaction of the character of curiosity in class VII students of SMP Negeri 8 Singkawang reached 82.48% in the high category. (3) The impact on students who have a curious character in class VII of SMP Negeri 8 Singkawang reaches 84.02% in the high category. (4) The efforts made by the counseling teacher in dealing with the curious character of class VII students at SMP Negeri 8 Singkawang achieved a result of 85.39% in the high category. The general conclusion is that the character of taste that class VII students of Singkawang State Middle School 8 want to know is in the high category with a proportion of 82.07%.